2023
DOI: 10.1186/s13007-023-01006-0
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane potential, an indicator in situ reporting cellular senescence and stress response in plant tissues

Abstract: Background Plant cells usually sustain a stable membrane potential due to influx and/or efflux of charged ions across plasma membrane. With the growth and development of plants, different tissues and cells undergo systemic or local programmed decline. Whether the membrane potential of plasma membrane could report senescence signal of plant tissues and cells is unclear. Results We applied a maneuverable transmembrane potential (TMP) detection method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 86 publications
1
0
0
Order By: Relevance
“…NaCl caused hyperpolarization in the root; KCl and sorbitol caused depolarization. Previously, other researchers reported that salinity caused depolarization in tobacco [64] or hyperpolarization in Arabidopsis [65], and sorbitol caused hyperpolarization in tobacco [64] and Arabidopsis [66]. Our results may indicate species-specific features of the reaction in different plants [67].…”
Section: Salt-induced Root-to-shoot Signalssupporting
confidence: 64%
“…NaCl caused hyperpolarization in the root; KCl and sorbitol caused depolarization. Previously, other researchers reported that salinity caused depolarization in tobacco [64] or hyperpolarization in Arabidopsis [65], and sorbitol caused hyperpolarization in tobacco [64] and Arabidopsis [66]. Our results may indicate species-specific features of the reaction in different plants [67].…”
Section: Salt-induced Root-to-shoot Signalssupporting
confidence: 64%